PENERAPAN SANKSI HUKUM BAGI PARA ADVOKAT PELAKU TINDAK PIDANA SUAP DALAM SISTEM HUKUM POSITIF DI INDONESIA - Hartono Hartono (JCH (Jurnal Cendekia Hukum), 2019)
Current bribery is very much happening in various regions of Indonesia and this can be seen from the increasingly widespread acts of abuse and abuse of the authority of law enforcement officers and can not be separated from the various things that make the occurrence of various bribery and wrong actions the other is done by Advocates who are part of one of the law enforcement officers in Indonesia, Advocates should be an example for the community and other law enforcement officials to obey and enforce the law. This research was conducted using normative juridical and statute approach, conducting studies on applicable laws and regulations and other regulations relating to the subject matter discussed in this research. The results of this study indicate that the application of sanctions to Advocates as perpetrators of bribery is subject to criminal penalties as stipulated in (Criminal Law, bribery law andthe law to eradicate corruption) and also the application of sanctions for Advocates' Code of Ethics.